(untitled) (Medico Legal Update, 2020)
Gestational diabetes mellitus (GDM) constitutes carbohydrate metabolism disorders that lead to severe and sometimes life-threatening complications of pregnancy. Materials and Method: 40 placenta biopsies with blood samples were taken from gestational diabetic pregnant women and 20 placenta biopsies with blood samples were taken from healthy pregnant women, the tissues were fixed, processed, embedded and cutting separately depending on procedure for enzyme histochemical and routine histological technique and the blood was centrifuged. Results: The histological changes in the GDM group represented by villous oedema in approximately (30%) of the GDM group, an excessive amount of collagen fibres in the villous stroma (57.5%). Syncytial knots were formed (70 %) in addition to an excessive number of cytotrophoblast cells in about (65 %). The stromal fibrinoid deposition was noticed in (52.5 %). Hypo-vascular villi are seen in (32.5%) also, atherosis of the uteroplacental arteries in (40%) of biopsies. In enzyme histochemistry, the villous stroma of the GDM group has a strong reaction to the G-6-P enzyme. There is a significant increase (p<0.05) in serum blood sugar, cholesterol, blood urea in the GDM group when compared with the normoglycemic group. Conclusions: The increment of serum blood sugar caused histological and enzyme histochemical alteration during pregnancies.